Efek Curcumin Sebagai Pengobatan Penyakit Jantung Koroner - Anggun Elidiya; Rizki Hanriko; M. Yusran (Medula, 2019)
Atherosclerosis is a chronic and progressive problem due to the inflammatory response, oxidative stress (OS), lipid deregulation, and epigenetic disorders. Curcumin is the main compound in turmeric and is responsible for turmeric yellow and contains 50% of turmeric. Curcumin has a hypolipidemic effect along with antioxidant and anti-inflammatory, it can contribute to reduce the incidence of atherosclerosis. The extraordinary antioxidant content of curcumin reduces lipid peroxidation and oxLDL formation, and consequently, reduces the inflammatory response and the development of atherosclerosis. Another study shows that curcumin can alter gene expression associated with leukocyte adhesion and transendothelial migration in aortic tissue by increasing expression of NF-κB protein inhibitors (IκB) and decreasing NF-κB bonds and transcription activity after stimulation with tumor necrosis factor-α (TNF-α). In addition, it is proven that curcumin can regulate the activation of toll-like receptor 4 (TLR4), a receptor that recognizes exogenous or endogenous molecular patterns and modulates immune and inflammatory responses. The role of other curcumin for atherosclerosis is smooth muscle cell proliferation. Curcumin is an antioxidant that can be one of the management of coronary heart disease due to be able to suppress the formation of atherosclerosis and reduce cholesterol levels in the blood. It is expected that curcumin can be the first treatment for coronary heart disease.